India's HIV programme: successes and challenges - Sukarma Tanwar; B.B. Rewari; C.V. Dharma Rao; Nicole Seguy (Elsevier, 2016)
Over the last two decades, India's National AIDS Control Programme (NACP) has evolved and expanded to provide HIV prevention, testing and treatment services countrywide. Scaling up has been uniform across all strategic components and has not only halted, but also reversed, the spread of the epidemic and ensured a major reduction in the number of AIDS-related annual deaths. As the epidemic has been driven by key populations, there was a special focus on these groups from the outset, with various innovative strategies for prevention and testing services. The treatment component has also been scaled up over the years through various models of service delivery that ensured access to free antiretroviral therapy for eligible HIV-infected patients. The programme, now in its fourth phase, has to ensure that new policies and strategies are developed in view of the global UNAIDS targets. The scale up over the years has ensured access to services; however, it is now important to ensure the quality and sustainability of newer models of interventions to ensure that the 2030 sustainable development goals are achieved.